The Role of State-Contingent Debt Instruments in Sovereign Debt Restructurings - Cohen, Charles; Abbas, S. M. Ali.; Anthony, Myrvin; Best, Tom. (Washington, D.C. : International Monetary Fund, 2020)
The COVID-19 crisis may lead to a series of costly and inefficient sovereign debt restructurings. Any such restructurings will likely take place during a period of great economic uncertainty, which may lead to protracted negotiations between creditors and debtors over recovery values, and potentially even relapses into default post-restructuring. State-contingent debt instruments (SCDIs) could play an important role in improving the outcomes of these restructurings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet